Emergency Department Treatment Provides Immediate and Durable Relief Following Vaccine Injury: A Case Report - Adam Rowh; Marta Rowh; Mark Goodman (Clinical Practice and Cases in Emergency Medicine, 2023)
Introduction: Intramuscular administration of vaccines into the deltoid muscle is the recommended route for most vaccines in adults. Ectopic injection into the subdeltoid/subacromial bursa can produce an inflammatory bursitis that is associated with significant long-term morbidity. Case Report: We describe a novel approach to treatment of this condition: ultrasound-guided administration of dexamethasone by the emergency physician within six hours of vaccine administration. This approach resulted in complete and durable long-term resolution of symptoms with no functional impairment. Conclusion: This outcome is superior to that described for usual care, and the approach is well-suited to emergency physicians.